Prenatal diagnosis of chromosomal abnormalities - Quiroga de Michelena, María (2015)
INTRODUCTION. Early prenatal diagnosis of chromosomal anomalies requires invasive techniques such as amniocentesis and chorionic villous sampling. We present our experience and the predictive value of ultrasonographic risk markers. DESIGN. Descriptive, transversal study. SETTING. Instituto Latinoamericano de Salud Reproductiva, Lima, Peru. BIOLOGIC SAMPLES. Amniotic fluid and placenta. INTERVENTIONS. We analyzed the results of 163 amniocentesis and 12 chorionic villous sampling performed at our institute between January 2003 and September 2007. MAIN OUTCOME MEASURES. Chromosome anomalies. RESULTS. The most frequent indication for prenatal invasive techniques was maternal age above 38 years; 48 (27,9%) of the samples obtained were positive for chromosomal anomalies and trisomy 21 the most common finding. The highest frequency of chromosomal anomalies was found in pregnancies with more than one ultrasonographic marker; cystic higroma was the most frequent marker. CONCLUSIONS. Ultrasonographic markers are important inclusion criteria in prenatal diagnosis patients’ selection. Cystic higroma and abnormal nuchal translucency showed the highest predictive values.